Surfing the SAW: Visualizing the oscillation of Au(111) surface atoms - Hesjedal, T; Chilla, E; Frohlich, H (IEEE, 1997)
In this paper we report the observation of surface acoustic waves using a scanning tunneling microscope (STM). As the STM's control electronics has a bandwidth limit in the kHz range, SAWs at typical frequencies of MHz to GHz cause a loss of contrast which can be clearly seen on an atomic scale. In order to access the amplitude and phase of a SAW, we introduced a heterodyning type STM, the scanning acoustic tunneling microscope (SATM). Contrary to the STM technique, the SATM measures snapshots of the state of oscillation. On the nanometer scale, two contributions to the phase and amplitude contrast are discussed. First, the SAWs phase delay gives a mainly linear dependence on the distance of the source. Second, the atomic oscillation trajectories within the SAW lead to a signal contribution that is made up of the shape of the oscillation trajectory and the local topography. On an atomic scale where the influence of the phase delay on the contrast can be neglected the oscillation trajectories of single surface atoms are studied. Finally, the atomically resolved phase and amplitude images are compared to simulated data.